Effects of irrigation patterns and nitrogen levels on the dynamic changes of nitrogen concentration in percolation water in a paddy field - CHEN Xing; LI Ya-juan; LIU Li; FANG Su-ping; FANG Ping; LIN Xian-yong (浙江大学学报. 农业与生命科学版, 2012)
A two-year pot experiment was conducted to investigate the effects of irrigation patterns and nitrogen (N) fertilizer levels on N leaching in paddy soils in a rice-wheat rotation cropping system. The experiment was designed with four levels of N fertilizer rates of N0, N1, N2, and N3 (0, 126, 157.5, and 210 kg·hm-2, respectively) in two irrigation patterns (FW: flooding water to a depth of 3 cm above soil surface and CW: keeping soil moisture but not ponding at soil surface). The rice variety II You 838 and alluvial soils from Hubei Province were used in this experiment. The results showed that the concentration of total N (TN) in percolation water decreased gradually during the rice growing season, and the risk of N leaching loss mainly appeared on the 40th day after transplanting. NO3--N and soluble organic nitrogen (SON) were the major forms of N in soil percolation water, while NH4+-N had a lower proportion compared with NO3--N and SON. The concentration of NO3--N reached the highest level during the 20th day to 30th day after transplanting, and the concentrations of NO3--N in soil percolation water increased as the N level increased during this period. Compared to N 3 (local recommendation dosage), the N2 treatment (75% of N3) under both irrigation patterns significantly increased the nitrogen use efficiency (NUE) and decreased leaching loss of N.